Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To show that [tex]\(\cos \left(x+45^{\circ}\right) \cos \left(x-45^{\circ}\right) = \frac{1}{2} \cos 2x\)[/tex], we can utilize trigonometric identities and properties. Here is a step-by-step solution:
1. Expression Setup: We start with the left hand side (LHS) of the equation:
[tex]\[ \cos \left(x + 45^\circ \right) \cos \left(x - 45^\circ \right) \][/tex]
2. Apply Trigonometric Identity: There is a trigonometric identity that relates the product of cosines to the sum of cosines:
[tex]\[ \cos(A) \cos(B) = \frac{1}{2} \left[ \cos(A + B) + \cos(A - B) \right] \][/tex]
For our problem, [tex]\(A = x + 45^\circ\)[/tex] and [tex]\(B = x - 45^\circ\)[/tex].
3. Simplify the Angles: Applying the identity with [tex]\(A = x + 45^\circ\)[/tex] and [tex]\(B = x - 45^\circ\)[/tex] gives us:
[tex]\[ \cos \left( x + 45^\circ \right) \cos \left( x - 45^\circ \right) = \frac{1}{2} \left[ \cos \left( (x + 45^\circ) + (x - 45^\circ) \right) + \cos \left( (x + 45^\circ) - (x - 45^\circ) \right) \right] \][/tex]
4. Combine the Angles: Simplifying inside the cosines:
[tex]\[ \cos \left( (x + 45^\circ) + (x - 45^\circ) \right) = \cos (2x) \][/tex]
[tex]\[ \cos \left( (x + 45^\circ) - (x - 45^\circ) \right) = \cos (45^\circ + 45^\circ - x + x) = \cos (90^\circ) \][/tex]
5. Evaluate [tex]\(\cos(90^\circ)\)[/tex]: We know that:
[tex]\[ \cos(90^\circ) = 0 \][/tex]
6. Substitute Back: Substituting the simplified expressions back into the identity we get:
[tex]\[ \cos ( (x + 45^\circ) + (x - 45^\circ) ) = \cos (2x) \][/tex]
[tex]\[ \cos ( (x + 45^\circ) - (x - 45^\circ) ) = \cos (90^\circ) = 0 \][/tex]
7. Final Simplification: This simplifies our expression to:
[tex]\[ \cos \left( x + 45^\circ \right) \cos \left( x - 45^\circ \right) = \frac{1}{2} \left[ \cos (2x) + 0 \right] = \frac{1}{2} \cos 2x \][/tex]
Thus, we have shown that:
[tex]\[ \cos \left(x + 45^\circ\right) \cos \left(x - 45^\circ\right) = \frac{1}{2} \cos 2x \][/tex]
1. Expression Setup: We start with the left hand side (LHS) of the equation:
[tex]\[ \cos \left(x + 45^\circ \right) \cos \left(x - 45^\circ \right) \][/tex]
2. Apply Trigonometric Identity: There is a trigonometric identity that relates the product of cosines to the sum of cosines:
[tex]\[ \cos(A) \cos(B) = \frac{1}{2} \left[ \cos(A + B) + \cos(A - B) \right] \][/tex]
For our problem, [tex]\(A = x + 45^\circ\)[/tex] and [tex]\(B = x - 45^\circ\)[/tex].
3. Simplify the Angles: Applying the identity with [tex]\(A = x + 45^\circ\)[/tex] and [tex]\(B = x - 45^\circ\)[/tex] gives us:
[tex]\[ \cos \left( x + 45^\circ \right) \cos \left( x - 45^\circ \right) = \frac{1}{2} \left[ \cos \left( (x + 45^\circ) + (x - 45^\circ) \right) + \cos \left( (x + 45^\circ) - (x - 45^\circ) \right) \right] \][/tex]
4. Combine the Angles: Simplifying inside the cosines:
[tex]\[ \cos \left( (x + 45^\circ) + (x - 45^\circ) \right) = \cos (2x) \][/tex]
[tex]\[ \cos \left( (x + 45^\circ) - (x - 45^\circ) \right) = \cos (45^\circ + 45^\circ - x + x) = \cos (90^\circ) \][/tex]
5. Evaluate [tex]\(\cos(90^\circ)\)[/tex]: We know that:
[tex]\[ \cos(90^\circ) = 0 \][/tex]
6. Substitute Back: Substituting the simplified expressions back into the identity we get:
[tex]\[ \cos ( (x + 45^\circ) + (x - 45^\circ) ) = \cos (2x) \][/tex]
[tex]\[ \cos ( (x + 45^\circ) - (x - 45^\circ) ) = \cos (90^\circ) = 0 \][/tex]
7. Final Simplification: This simplifies our expression to:
[tex]\[ \cos \left( x + 45^\circ \right) \cos \left( x - 45^\circ \right) = \frac{1}{2} \left[ \cos (2x) + 0 \right] = \frac{1}{2} \cos 2x \][/tex]
Thus, we have shown that:
[tex]\[ \cos \left(x + 45^\circ\right) \cos \left(x - 45^\circ\right) = \frac{1}{2} \cos 2x \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.